Randomized, controlled trial of 2 L polyethylene glycol plus ascorbate components versus sodium phosphate for bowel cleansing prior to colonoscopy for cancer screening. (December 2014) - Ell, C.; Fischbach, W.; Layer, P.; Halphen, M.
Abstract Background: Colonoscopy requires effective bowel preparation for adequate mucosal visualization. Safety and acceptability of bowel preparation are key components in colorectal cancer screening (CRC) populations. Objective: To compare the efficacy, safety and acceptability of bowel preparation with polyethylene glycol (PEG), ascorbic acid, sodium ascorbate (ascorbate components), sodium sulfate and electrolytes (PEG+Asc) or sodium phosphate (NaP). Methods: Consenting adults undergoing elective out-patient colonoscopy for CRC were randomized to take 2 L PEG+Asc or 90 mL NaP (control) following manufacturer's instructions. PEG+Asc was taken the evening before and morning of the colonoscopy; NaP was taken the morning and evening before colonoscopy. Participants followed a restricted diet specific to each preparation. Primary endpoint was bowel cleansing success (100% colon mucosa visible) rated by an independent expert panel (all experienced endoscopists) unaware of treatment allocations. Subject reported outcomes about the preparations were elicited. Adverse events were recorded. Clinical trial registration: Clinicaltrials.gov: NCT00427089. Results: Successful bowel cleansing rate was significantly higher in the PEG+Asc (N = 242) than the NaP (N = 114) group (PEG+Asc 93.4% [95% CI 89.5–96.2] versus NaP 22.8% [15.5–31.6%], p < 0.0001). Subject reported outcomes on acceptability of the two different preparations were not significantly different (p = 0.238). However, taste ratings for PEG+Asc were significantly better versus NaP (mean VAS: 31.2 and 38.1 respectively, p = 0.0111). The proportion of patients prepared to receive the same preparation again was significantly higher in the PEG+Asc group (88.4% vs. 78.1%, p < 0.0001). Conclusions: PEG+Asc provided superior bowel cleansing to NaP and was well tolerated. Findings for PEG+Asc are aligned with previous similar studies; however, differences observed in NaP cleansing results, especially for the proximal colon segments, may be due to factors including: differences in demographics and population types and the use of the validated Harefield Cleansing Scale as an assessment tool combined with expert reviews, which may have resulted in conservative cleansing assessments.